2023
DOI: 10.1097/ta.0000000000003907
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department versus operating room intubation of patients undergoing immediate hemorrhage control surgery

Abstract: BACKGROUNDHemorrhage control surgery is an essential trauma center function. Airway management of the unstable bleeding patient in the emergency department (ED) presents a challenge. Premature intubation in the ED can exacerbate shock and precipitate extremis. We hypothesized that ED versus operating room intubation of patients requiring urgent hemorrhage control surgery is associated with adverse outcomes at the patient and hospital-levels.METHODSPatients who underwent hemorrhage control within 60 minutes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…This retrospective cohort study using the US National Trauma Data Bank identified adult patients transferred to the operating theatre for HCS within 60 min of hospital arrival and compared in-hospital mortality among those intubated in the ED versus in theatre. The authors also performed a hospital-level analysis comparing mortality in hospitals with high versus low tendency for ED intubation 5…”
Section: Emergency Department Vs Operating Room Intubation Of Patient...mentioning
confidence: 99%
“…This retrospective cohort study using the US National Trauma Data Bank identified adult patients transferred to the operating theatre for HCS within 60 min of hospital arrival and compared in-hospital mortality among those intubated in the ED versus in theatre. The authors also performed a hospital-level analysis comparing mortality in hospitals with high versus low tendency for ED intubation 5…”
Section: Emergency Department Vs Operating Room Intubation Of Patient...mentioning
confidence: 99%
“…The patients intubated in the ED are more severe (median injury severity score 22 Vs 17, p < 0.001) and more frequently suffer chest trauma (50% Vs 34.6%, p < 0.001) than those intubated in the OR. 1 However, we have no clinical (saturation or respiratory rate) or paraclinical (arterial blood gas) data to determine their degree of respiratory failure. There is a great risk of comparing patients who present a double failure, respiratory and circulatory, with patients presenting only a circulatory failure.…”
mentioning
confidence: 99%
“…The analysis of 9,667 patients shows that patients intubated in the ER die significantly more than those intubated in the OR (17.4% Vs 7.1%, p < 0.001). 1 To minimize confounding, the authors take the choice to exclude patients deadon-arrival, undergoing ED thoracotomy, or with clinical indications for intubation (severe head/neck/face injury or GCS <8). 1 Despite this, a certain number of missing elements, whether in the profile of the patients or the timeline of their management, limit us in the analysis of the results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thank you to Corcostegui et al for their interest in our recent article entitled “Emergency Department Versus Operating Room Intubation of Patients Undergoing Immediate Hemorrhage Control Surgery” 1 …”
mentioning
confidence: 99%